Influence of Power Distribution on Surface Temperature Homogeneity in Aluminium Hot-Plate Heaters for PVC Window Welding - Kibar, Ali; Öztürk, Eyüp; Albayrak, M (Fırat University, 2026)
The surface temperature uniformity of aluminium hot?plate heaters is a key factor affecting weld quality in PVC hot?plate welding. Although aluminium plates are widely preferred for their high thermal conductivity, the effect of internal power distribution on surface temperature homogeneity under constant total power has not been thoroughly quantified. This study investigates the transient thermal behaviour of an aluminium heating plate using a three?dimensional numerical heat conduction model including internal heat generation and convection–radiation losses. Two power?distribution scenarios—symmetric (1250–1250 W) and asymmetric (1000–1500 W)—were examined with a fixed total power of 2500 W. Both reached the target temperature of 240 °C in similar times (~321 s), showing that overall heating behaviour is dictated mainly by total input power. However, spatial temperature differences were significant. The symmetric case produced global surface variations of ~30 °C, whereas the asymmetric case reduced this range to ~18 °C. In the active welding zone, temperature variation decreased from ~15 °C (symmetric) to only 4–5 °C (asymmetric). These results demonstrate that heat?flux balance, rather than electrical symmetry, governs temperature uniformity. Therefore, internal power distribution represents an independent thermal design parameter and provides a practical basis for optimizing aluminium hot?plate heaters used in industrial PVC welding systems.

Alüminyum sıcak?plaka ısıtıcıların yüzey sıcaklığı homojenliği, PVC sıcak?plaka kaynağında kaynak kalitesini doğrudan etkileyen temel bir parametredir. Alüminyum plakalar yüksek ısıl iletkenlikleri nedeniyle yaygın olarak kullanılmasına rağmen, sabit toplam güç altında iç güç dağılımının yüzey sıcaklık homojenliğine etkisi yeterince nicel olarak incelenmemiştir. Bu çalışmada, iç ısı üretimi ve konveksiyon?radyasyon kayıplarını içeren üç boyutlu zamana bağlı bir ısı iletimi modeli kullanılarak bir alüminyum sıcak?plaka ısıtıcısının termal davranışı analiz edilmiştir. Toplam güç 2500 W sabit tutulmak üzere iki senaryo—simetrik (1250–1250 W) ve asimetrik (1000–1500 W) incelenmiştir. Her iki durumda da hedef sıcaklık olan 240 °C’ye benzer sürelerde (~321 s) ulaşılmış, böylece küresel ısınma davranışının esas olarak toplam güç girdisi tarafından belirlendiği doğrulanmıştır. Ancak uzamsal sıcaklık dağılımları belirgin şekilde farklıdır. Simetrik dağılım ~30 °C’lik bir yüzey sıcaklık aralığı oluştururken, asimetrik dağılım bu aralığı ~18 °C’ye düşürmüştür. Aktif kaynak bölgesinde sıcaklık değişimi simetrik durumda ~15 °C iken, asimetrik durumda 4–5 °C seviyesine inmiştir. Sonuçlar, sıcaklık homojenliğinin elektriksel simetriden ziyade ısı akısı dengesine bağlı olduğunu göstermekte ve güç dağılımının bağımsız bir termal tasarım parametresi olduğunu ortaya koymaktadır.
PVC Pencere Kaynağı için Alüminyum Sıcak-Plaka Isıtıcılarda Güç Dağılımının Yüzey Sıcaklığı Homojenliğine Etkisi
Keywords: Computational Methods in Fluid Flow; Heat and Mass Transfer (Incl. Computational Fluid Dynamics); Akışkan Akışı; Isı ve Kütle Transferinde Hesaplamalı Yöntemler (Hesaplamalı Akışkanlar Dinamiği Dahil)